Analysis of Determinants of Employee Performance: A Case Study - Basuki, Tri Wiyana; Sri Wahyuni; Tubastuvi, Naelati; Fitriati, Azmi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
This study aims to analyze and find empirical evidence that leadership style, supervision, work discipline, motivation, bonuses, and incentives on employee performance. This type of research is quantitative research. The population in this study were all employees of PT. Green Lahat, totaling 114 people. The data used in this study is primary data. Methods of data collection are done by using a questionnaire. The analysis technique used is multiple linear regression analysis. The results showed that leadership style, supervision, work discipline, motivation, bonuses, and incentives had a positive effect on employee performance. PT. Green Lahat needs to improve leadership and supervisory styles so that work discipline and employee motivation increase so that employee performance will also increase. In addition, PT. Green Lahat should maintain a system of distribution of bonuses and incentives so that employees can further improve their performance.